Perencanaan Taman Edukasi Menuju Desa Pademawu Timur Mandiri - Iswahyudi Iswahyudi; Marchel Putra Garfansa; Yenni Arista Cipta Ekalaturrahmah (Institut Pertanian Bogor, 2022)
This Community Service Program (PKM) is implemented based on a Memorandum of Agreement (MoA) between the Agrotechnology Study Program, Faculty of Agriculture, Madura Islamic University and East Pademawu Village. The coaching program carried out is related to landscape learning materials. The purpose of providing landscape design materials for East Pademawu BUMDes is to improve landscape design insight and skills, to optimize the function and beauty and role of local village education parks so that they can support BUMDes administrators towards independent villages. Service activities in the form of providing materials and training followed by distributing questionnaires (based on a Likert scale whose score has been determined) to measure the level of achievement of socialization and training carried out. The location for the design is the backyard of the East Pademawu Village Hall office. The results of the participants' assessment of the benefits of the training through observation sheets showed an increase in the benefits, soft skills of BUMDes participants and the quality of local village facilities and infrastructure with a percentage of 83%. Participants showed enthusiasm and activity in the good category and agreed on the educational park landscape plan that had been optimally designed on village land. However, for mastery of material, creativity and conveying ideas, participants fall into the sufficient category so that there is a need for guidance and retraining which is based on the approval of cooperation between partner members and the garden landscape design team of the Madura Islamic University so that periodic guidance for BUMDes can still be carried out. The shortcoming that still needs to be considered for participants is a sense of design which can be overcome and minimized by broadening their horizons and actively joining the landscape design community.